A framework for the automatic identification of algae (Neomeris vanbosseae M.A. Howe):U3S - Tan, C.S. (Institute of Electrical and Electronics Engineers Inc., 2014)
Neomeris vanbosseae M.A. Howe (NVH) is an algae belonging to the Chlorophyta, which is a very diverse group of algae. Therefore when an algae biologist establishes an abundance assessment for algae biodiversity, the taxonomic identification and quantification could frequently lead to a time intensive procedure which is prone to a counting bias, due to fatigue when processing large pools of data samples repeatedly. To improve the effectiveness, this paper proposed a framework, being an assistive tool, to help marine biologists. The framework consists of (1) pre-processing the image, (2) segmenting region of interest, (3) extracting features (namely four different geometric features), (4) evaluating and combining those features based on the given decision criterions, and (5) the quantification. Our methodology achieved satisfactory performance (NVH abundance) as it's able to provide an encouraging result with 78.38 detection rate yielded by the comparison between manual count and our system automatic count. The major contribution of this work is the development and the deployment of an automatic identification system, named U3S, for biodiversity abundance studies of algae to assist the marine biologist in identifying algae species, complementing the existing operator intensive proceduResearch Â© 2014 IEEE.